Martin Van Buren papers - Van Buren, Martin, 1782-1862.; Van Buren, John, 1810-1866.
Correspondence, drafts of writings, speeches, and messages to Congress, autobiographical material, notes, legal record book, estate record book, and other papers pertaining to slavery and the antislavery movement; banking and the Second Bank of the United States; party politics in New York state and at the national level relating to the Federalist, National Republican, Whig, and Democratic parties, particularly during the Jackson and Van Buren administrations; and the opposition politics of John C. Calhoun, Henry Clay, DeWitt Clinton, William Henry Harrison, Winfield Scott, Zachary Taylor, John Tyler, and Daniel Webster. Other topics include the Washington Globe, Indian affairs, the annexation of Texas and war with Mexico, Free Soil Movement, tariffs, relations with France and England, and the northeast boundary question. Also includes material pertaining to Van Buren's home, Lindenwald, in Kinderhook, N.Y., and correspondence and a travel journal (1838-1839) kept by John Van Buren during a trip to England and Europe.
Of particular significance is the correspondence (1828-1845) with Andrew Jackson. Other correspondents include George Bancroft, Thomas Hart Benton, Francis Preston Blair, James Buchanan, Benjamin F. Butler, Harriet Allen Butler, Churchill Caldom Cambreleng, John A. Dix, John Fairfield, Azariah C. Flagg, Henry D. Gilpin, James Hamilton, Jr., Jesse Hoyt, Charles Jared Ingersoll, Amos Kendall, William L. Marcy, Louis McLane, Richard Elliot Parker, James Kirke Paulding, Joel Roberts Poinsett, James K. Polk, Thomas Ritchie, William C. Rives, Andrew Stevenson, Levi Woodbury, and Silas Wright.
Microfilm edition of series 1-7 and a portion of series 8 available
Microfilm produced from originals in the Manuscript Division.
In part, transcripts.
U.S. president, vice-president, secretary of state and senator from New York.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bancroft, George, -- 1800-1891 -- Correspondence; Benton, Thomas Hart, -- 1782-1858 -- Correspondence; Blair, Francis Preston, -- 1791-1876 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Butler, Benjamin F. -- 1795-1858 -- Correspondence; Butler, Harriet Allen -- Correspondence; Calhoun, John C. -- 1782-1850.; Cambreleng, Churchill Caldom, -- 1786-1862 -- Correspondence; Clay, Henry, -- 1777-1852.; Clinton, DeWitt, -- 1769-1828.; Dix, John A. -- 1798-1879 -- Correspondence; Fairfield, John, -- 1797-1847 -- Correspondence; Flagg, Azariah C. -- 1790-1873 -- Correspondence; Gilpin, Henry D. -- 1801-1860 -- Correspondence; Hamilton, James, -- 1786-1857 -- Correspondence; Harrison, William Henry, -- 1773-1841.; Hoyt, Jesse -- Correspondence; Ingersoll, Charles Jared, -- 1782-1862 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Jackson, Andrew, -- 1767-1845 -- Correspondence; Kendall, Amos, -- 1789-1869 -- Correspondence; Marcy, William L. -- 1786-1857 -- Correspondence; McLane, Louis, -- 1786-1857 -- Correspondence; Parker, Richard Elliot, -- 1783-1840 -- Correspondence; Paulding, James Kirke, -- 1778-1860 -- Correspondence; Poinsett, Joel Roberts, -- 1779-1851 -- Correspondence; Polk, James K. -- 1795-1849 -- Correspondence; Ritchie, Thomas, -- 1778-1854 -- Correspondence; Rives, William C. -- 1793-1868 -- Correspondence; Scott, Winfield, -- 1786-1866.; Stevenson, Andrew, -- 1784-1857 -- Correspondence; Taylor, Zachary, -- 1784-1850.; Tyler, John, -- 1790-1862.; Van Buren, Martin, -- 1782-1862 -- Homes and haunts; Webster, Daniel, -- 1782-1852.; Woodbury, Levi, -- 1789-1851 -- Correspondence; Wright, Silas, -- 1795-1847 -- Correspondence; Bank of the United States (1816-1836); Democratic Party (U.S.); Federal Party (U.S.); Free Soil Party (U.S.); National Republican Party (U.S.); Whig Party (U.S.); Indians of North America -- Government relations; Mexican War, 1846-1848.; Slavery -- United States; Tariff -- United States; Dwellings -- New York (State) -- Kinderhook; Canada -- Boundaries -- United States; England -- Description and travel; Europe -- Description and travel; France -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; New York (State) -- Politics and government -- 1775-1865.; Northeast boundary of the United States; Texas -- Annexation to the United States; United States -- Boundaries; United States -- Boundaries -- Canada; United States -- Foreign relations -- France; United States -- Foreign relations -- Great Britain